Analisis Makna Referensial dan Nonreferensial dalam Umpasa Batak Toba - Roslina Mariana Butarbutar; Ernanda Ernanda; Julisah Izar (Prodi Sastra Indonesia, FKIP Universitas Jambi, 2023)
Abstrak Penelitian ini bertujuan untuk mendeskripsikan makna referensial dan nonreferensial dalam umpasa Batak Toba yang terdapat dalam upacara-upacara Batak Toba yaitu dalam upacara pernikahan, kelahiran, kematian, memasuki rumah dan baptisan kudus. Jenis penelitian yang digunakan adalah penelitian deskriptif kualitatif. Data dalam penelitian ini berupa kata dalam umpasa Batak Toba yang mengandung makna referensial dan nonreferensial. Teknik yang digunakan dalam penelitian ini ialah teknik pilah unsur penentu, wawancara, dan teknik rekam. Hasil penelitian ditemukan makna referensial dan nonreferensial sebanyakÂ 44 umpasa. Dari 44 data umpasa ditemukan 14 data bermaknakan referensial. Referensial ialah makna yang berhubungan langsung dengan acuan yang ditunjuk oleh kata. Referen ataupun acuan boleh saja berupa benda, gejala, peristiwa, proses, sifat ataupun kenyataan. Adapun makna referensial yang mengacu pada benda terdapat 13 data, makna referensial yang mengacu pada sifat berjumlah 1 data. Adapun makna nonreferensial dalam penelitian ini ditemukan 8 data. Dikatakan makna nonreferensial jika kata-kata tidak memiliki acuan/referen dan kata tugas merupakan makna nonreferensial yakni seperti pada kata tugas preposisi dan konjungsi serta relative marker (penanda relatif). Dari 8 data makna nonreferensial ditemukan penghubung koordinatif pertentangan berjumlah 1. Makna referensial pada penghubung koordinatif penggabungan 3. Makna nonreferensial pada penghubung koordinatif pemilihan berjumlah 1. Makna nonreferensial pada penghubung subordinatif penyebab berjumlah 1. Makna nonreferensial pada penghubung subordinatif syarat berjumlah 1. Makna nonreferensial relative marker berjumlah 1. Adapun makna referensial dan nonreferensial ditemukan 22 data yakni makana referensial dengan preposisi ke- ada 2 data. Makna referensial dengan preposisi di- ada 1 data. Makna referensial dengan konjungsi koordinatif penggabungan ada 10 data. Makna referensial dengan konjungsi koordinatif pertentangan ada 1 data. Makna referensial dengan dengan konjungsi subordinatif tujuan ada 2 data. Makna referensial dengan relative marker (penanda relatif) ada 6 data. Jadi, dalam umpasa Batak Toba sering menggunakan makna referensial dengan konjungsi koordinatif penggabungan. Abstract This study aims to describe the referential and nonreferential meanings in the Batak Toba umpasa contained in the Batak Toba ceremonies, namely in the ceremonies of marriage, birth, death, entering the house and holy baptism. The type of research used is qualitative descriptive research. The data in this study is in the form of words in umpasa Batak Toba which contain referential and nonreferential meanings. The techniques used in this study are the determinant element sorting technique, interviews, and recording techniques. The results of the study found referential and nonreferential meanings of 44 umpasa. Of the 44 data, 14 data were found to be referential. Referential is a meaning that is directly related to the reference designated by the word. References or references may be objects, symptoms, events, processes, properties, or realities. As for the referential meaning that refers to objects, there are 13 data, the referential meaning that refers to the nature of 1 data.Â As for the nonreferential meaning in this study, 8 data were found. It says a nonreferential meaning if the words do not have a reference / referent and the word task is a nonreferential meaning that is as in the word task preposition and conjunction and relative marker (relative marker). From 8 nonreferential meaning data found coordinate links of opposition totaling 1. Referential meanings on the coordinate link of merging 3. The nonreferential meanings on the coordinate link of the election amount to 1. The nonreferential meanings on the subordinative link of the cause amount to 1. The nonreferential meaning on the subordinate link of the condition amounts to 1. The nonreferential meaning of relative marker amounts to 1. The referential and nonreferential meanings found 22 data, namely referential feeds with the preposition to- there are 2 data. Referential meaning with prepositions in- there is 1 data. The referential meaning with the coordinate conjunction of the merger there are 10 data. Referential meaning with coordinate conjunction of the opposition there is 1 data. The referential meaning with the subordinative conjunction of the purpose there are 2 data. The referential meaning with relative marker (relative marker) there are 6 data. Thus, in umpasa Batak Toba often uses referential meanings with coordinate conjunctions of merging.